MORPHOMETRY ANALYSIS OF SILAT SUB-WATERSHED BASED ON GEOSPATIAL TECHNOLOGY IN THE SILAT HULU SUB DISTRICT - Ramdhania, Nurul; Rianingsih, Ayu; Nurfitri, Holifah; Purwanto, Ajun; Andrasmoro, Dony; Eviliyanto, Eviliyanto; Francista, Francista; Rentia, Florensia (GeoEco, 2023)
This study aims to obtain morphometric data from the Silat sub-watershed. The method used is a survey and interpretation of secondary data. Secondary data is taken from Remote Sensing Images, Topographic Maps, and Administration maps. The morphometric data taken were the area, shape, circumstance, river length, river order, height, and drainage density. Data analysis using the Spatial Analyst Tool, namely Hydrology, Map Algebra, and Density tools from ArcGis 10.8. Based on the research results, it is known that the Silat watershed has an area of 466 km², a circumference of 147 km, and a river length of 51 km. The shape of the Silat watershed is elongated because the Circularity Ratio value is 0.27 (<0.5), and the Elongation Ratio value is 5.14 (round). The order of the river network is up to order 6, with a branching index (Rb) of order 1 = 2.03; 2nd order = 2.09; 3rd order = 1.75; 4th order = 1.84; and 5th order = 0.96. The Weighted Average Branching Index (WRb) was 2.73 (<3). The Silat sub-watershed has a height of 32 - 255 meters above sea level. Low river density, dendritic river flow pattern.